Leveraging Integrated Primary Care to Address Patients' and Families' Unmet Social Needs: Aligning Practice with National Academy of Sciences, Engineering and Medicine Recommendations - Poleshuck, Ellen; Possemato, Kyle; Johnson, Emily M; Cohen, Alicia J; Fogarty, Colleen T; Funderburk, Jennifer S (Journal of the American Board of Family Medicine, 2022)
Primary care is well-poised to address unmet social needs that affect health. Integrated primary care is increasingly common and can be leveraged to facilitate identification of practice and clinician-level modifiable characteristics and assist practices to address unmet social needs for patients and families. A recent National Academies of Sciences, Engineering, and Medicine (NASEM)'s consensus report identified 5 critical system-level activities to facilitate the integration of addressing social needs into health care: awareness (ask patients), adjustment (flexible intervention delivery), assistance (intervention to address the social need), alignment (link with community resources), and advocacy (policy change). This article outlines how integrated primary care characteristics, such as routine screening, functional workflows, interprofessional team communication, and patient-centered practices, exemplify the NASEM report's activities and offer robust biopsychosocial tools for addressing social needs. We provide a case to illustrate how these strategies might be used in practice.